Compliance assessment of tobacco vendors of Ahmedabad city to India’s Tobacco control legislation - Govil, Samarth; Dhyani, Anurag; Mall, Anjali S (Indian Journal of Community Health, 2016)
Background: Many worldwide strategies and efforts have been made to tackle the menace of tobacco use and related morbidity and mortality. On similar lines, Government of India enacted a law in 2003, Cigarette and Other Tobacco Products Act (COTPA, 2003). Aims & Objectives: To measure compliance to Section 5 & 6(a) of COTPA, 2003. Material & Methods: A cross-sectional survey at 432 Point of Sale (POS) across Ahmedabad city using random sampling technique. Results: Only 15.3% of the POS had complied with the size of their main display Board (MDB). Around one third (34%) of the shops had displayed the prescribed warning message on their MDB. More than half (53%) of the shops did not display any tobacco advertisement. The proportion of shops with no backlit/illumination MDBs was 30.3%. None of the POS complied with Section 6(a). More than a quarter of the POS (28%) were partial tobacco vendors. Proportion of mobile tobacco vendors was 22.9%. Conclusion: There has been a gross violation of Sections 5 & 6(a) of COTPA, 2003 across a majority of POS. This kind of laxity in compliance portrays a grim scenario of tobacco control and thus calls for immediate redressal by all the stakeholders involved.